BAHASA ARAB SEBAGAI BAHASA DIGLOSIS - Umi Nurun Ni’mah (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
Just like many centuries ago, the Arabic language today is under a “diglossic” situation. As a langue, it richly varies that among them are the “high” and the “low” –something that very common in a diglossic situation. The “high” is the formal variant, called fushā and the “low” is the colloquial spoken variant, called lahjah (dialect). This latest variant grows differently in many shapes that are not yet clearly classified as the linguists agree so far. The dichotomy between fushā-lahjah truly is not a new phenomenon in Arabic world as it has taken place since long ago. However, it has just become a serious problem lately. The dialectical Arabic growth of the lahjah with its plenty different variants in the centers of culture raises problems. This paper comes before you describing the general situation instead of the detail characteristic of every variant. Besides, herewith the discussion on the scientific attention on the matter of diglossic Arabic and —certainly— the problems it rises. The Arabic linguists pay so much attention to solve it for which the debates come largely. The unavoidable disagreements come into one of the three: keeping the fushā, contradicting it, or standing between. Some opinions are given for examples. However all out they have made their effort for it, it would remain a difficult problem without a serious consideration of all the Arab Unity on their own language. Therefore, the involvement of all of the Arabic states is absolutely needed.